2021
DOI: 10.1099/jgv.0.001531
|View full text |Cite
|
Sign up to set email alerts
|

PA-X is an avian virulence factor in H9N2 avian influenza virus

Abstract: Influenza A viruses encode several accessory proteins that have host- and strain-specific effects on virulence and replication. The accessory protein PA-X is expressed due to a ribosomal frameshift during translation of the PA gene. Depending on the particular combination of virus strain and host species, PA-X has been described as either acting to reduce or increase virulence and/or virus replication. In this study, we set out to investigate the role PA-X plays in H9N2 avian influenza viruses, focusing on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…Our results suggested that PA-X protein of H9N2 subtype AIVs was a virulence factor in facilitating viral pathogenicity which was consistence with the previous studies (Clements et al, 2021;Gao et al, 2015). For non-immune cells, PA-X protein enhanced the replication level of H9N2 subtype AIVs on MDCK cells, which probably due to the selectivity of PA-X host shut-off activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results suggested that PA-X protein of H9N2 subtype AIVs was a virulence factor in facilitating viral pathogenicity which was consistence with the previous studies (Clements et al, 2021;Gao et al, 2015). For non-immune cells, PA-X protein enhanced the replication level of H9N2 subtype AIVs on MDCK cells, which probably due to the selectivity of PA-X host shut-off activity.…”
Section: Discussionsupporting
confidence: 88%
“…Consistently, another independent study also found that PA-X protein of H9N2 subtype AIVs enhanced virus replication in produced mammalian cells, increased the pathogenicity in chicken embryos and caused more rapid viral shedding and widespread dissemination in birds (Clements et al, 2021).…”
Section: E3089supporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, to achieve an in-depth understanding of the influence on host immune cells, we successfully established an induction culture system of chBM-DCs in vitro, which provided a tool for studying the interconnection between avian pathogens and host immune responses. Some studies showed PA-X protein acts as a virulence factor for H9N2 subtype AIVs ( Gao et al., 2015 ; Clements et al., 2021 ). Moreover, PA-X protein selectively only to degrade the host's RNA through its endonuclease activity, but not the virus itself ( Hu et al., 2015 ; Nogales et al., 2017 ; Gaucherand, et al., 2019 ; Rigby et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…PA-X of H5N1 subtype AIVs is a negative virulence regulator that can reduce virulence by inhibiting viral replication and host innate immune responses ( Hu et al., 2015 ). In contrary, PA-X protein of H9N2 subtype AIVs, as a virulence factor, can improve the pathogenicity in mammals by enhancing virus replication, cell apoptosis, and lung injury ( Gao et al., 2015 ), and affect the embryos lethality and lead to more rapid shedding and visceral tropism in birds ( Clements et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%